2011
DOI: 10.1163/092050610x519471
|View full text |Cite
|
Sign up to set email alerts
|

α- and β-Poly(Vinylidene Fluoride) Evoke Different Cellular Behaviours

Abstract: α-Phase poly(vinylidene fluoride) (PVDF) has chains of zero dipole moments and is, therefore, nonpiezoelectric, while β-phase PVDF has the most significant piezoelectric properties among the polymorphs due to its polar chains. Although many reports describe PVDF as a suitable biomaterial due to its stability and biocompatibility, few considered the specific effects that the different polymorphs exert on cellular behaviour. We hypothesized that α- and β-phase PVDF will exert direct but different influences on c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 29 publications
2
42
0
Order By: Relevance
“…Contrarily, Low et al [166] found that α phase PVDF supports higher cell metabolic activity and cell spreading compared to the β phase. Recently, it was found that interestingly β phase PVDF membranes can provide the necessary electrical stimuli for the growth and proliferation of special cells [167].…”
Section: For Biomaterials and Tissue Engineeringmentioning
confidence: 99%
“…Contrarily, Low et al [166] found that α phase PVDF supports higher cell metabolic activity and cell spreading compared to the β phase. Recently, it was found that interestingly β phase PVDF membranes can provide the necessary electrical stimuli for the growth and proliferation of special cells [167].…”
Section: For Biomaterials and Tissue Engineeringmentioning
confidence: 99%
“…Bulk PVDF has a failure strain in the range of 12% -50% 26, 27 . In addition, PVDF is biocompatible and is considered a highly attractive polymer for biomedical applications such as in smart catheter devices and as scaffold for tissue engineering 28,29,30 .…”
Section: Introductionmentioning
confidence: 99%
“…Spin coating was used to obtain thin films of β-Phase [11][12][13]. α and β-Phase conformation were produced in PVDF thin films cast by varying solvent polarity (DMF and HMPA) respectively, evaporation rate and drying temperature 140 o C [14]. By crystallization at temperatures near the melting temperature (T m ) of the α-Phase, the γ-Phrase may be outcome [8,[15][16].…”
Section: Introductionmentioning
confidence: 99%